Co‐occurrence of genes encoding carbapenemase, ESBL, pAmpC and non‐β‐Lactam resistance among Klebsiella pneumonia and E. coli clinical isolates in Tunisia. (1st May 2022) - Ben Sallem, R.; Laribi, B.; Arfaoui, A.; Ben Khelifa Melki, S.; Ouzari, H. I.; Ben Slama, K.; Naas, T.; Klibi, N.
Abstract: This study aimed to investigate the molecular mechanisms of carbapenem and colistin resistance in K . pneumoniae and E . coli isolates obtained from hospitalized patients in Carthagene International Hospital of Tunis. A total of 25 K . pneumoniae and 2 E. coli clinical isolates with reduced susceptibility to carbapenems were recovered. Susceptibility testing and phenotypic screening tests were carried out. ESBL, AmpC, carbapenemase and other antibiotic resistance genes were sought by PCR‐sequencing. The presence of plasmid‐mediated colistin resistance genes ( mcr ‐1‐8) was examined by PCR and the nucleotide sequence of the mgrB gene was determined. The analysis of plasmid content was performed by PCR‐Based Replicon Typing (PBRT). The clonality of isolates was assessed by PFGE and multilocus sequence typing (MLST). All of the isolates produced carbapenemase activity. They showed a great variation in the distribution of ESBL, AmpC, carbapenemase and other plasmid‐mediated resistance determinants. K . pneumoniae isolates carried bla NDM‐1 ( n = 11), bla OXA‐48 ( n = 11), bla NDM‐1 + bla OXA‐48 ( n = 1), bla NDM‐1 + bla VIM‐1 ( n = 1), bla OXA‐204 ( n = 1), along with bla CTX‐M, bla OXA, bla TEM, bla CMY, bla DHA and bla SHV genes variants on conjugative plasmid of IncL/M, IncR, IncFIIK, IncFIB, and IncHI1 types. Three sequence types ST101, ST307 and ST15 were identified. The mgrB alteration g109a (G37S) was detected in a single colistin‐resistant, NDM‐1 and OXA‐48‐coproducing K. pneumoniae isolate. The two E . coli isolates belonged to ST95, co‐produced NDM‐1 and CTX‐M‐15, and harboured plasmid of IncFII and IncFIB types. To our knowledge, this is the first report in Tunisia of NDM‐1, OXA‐48, and CTX‐M‐15 coexistence in colistin‐resistant K . pneumoniae ST15. Abstract: Significance and Impact of the Study: Our data revealed multiple co‐expressed resistance determinants, including genes encoding carbapenemases, ESBLs, pAmpCs and non‐β‐Lactam resistance in all carbapenem resistance strains investigated. In the present study, we reported a high prevalence of bla  NDM‐1 among K. pneumoniae from Carthagene International Hospital of Tunis, mostly related to imported cases. These data urge for screening of patients coming abroad and strict contact isolation measures to stop the further spread in hospital settings.